Analytical solution for coupled water–gas transport in unsaturated landfill cover system with different root architectures. (February 2023) - Min, Ming; Pu, He-Fu; Feng, Song; Qiu, Jin-Wei; Wen, Xiao-Jun
Abstract: This study presents an analytical solution for coupled water–gas transport in a landfill cover system considering four different root architectures (i.e., uniform, triangular, exponential and parabolic architectures), which can consider transient diffusive-advective transport of gas under steady-state water distributions in different condition (e.g., rainfall stage and evaporation stage). The proposed solution is verified against an existing analytical solution, validated against an experiment, and compared with a numerical solution. Using the verified analytical solution, simulations were conducted on the coupled water–gas transport. The results show that ignoring water transport can lead to significant error in gas transport results under various conditions (e.g., the methane flux is underestimated by 45% due to ignoring water transport, when the desaturation coefficient α is 0.1 m −1 ). The parametric study results indicate that triangular and exponential root architectures have greater effect on water–gas transport (e.g., pore-water pressure, gas emission fluxes) compared with the uniform and parabolic root architectures; vegetation has a significant impact on the water–gas transport, especially in dry conditions (e.g., the gas emission flux through vegetated cover is about 26.3% lower than that through the bare cover); the rainfall intensity and volumetric water content at the bottom boundary have significant effect on water–gas transport in the cover. The proposed analytical solution can be used to aid the design of vegetated soil cover system and the verification of other more complex models.